The Impact of Product and Labour Market Reform on Growth: Evidence for OECD Countries Based on Local Projections - Jakob de Haan; Rasmus Wiese (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper examines the impact of labour and product market reforms on economic growth in 25 OECD countries between 1985 and 2013, and tests whether this impact is conditioned by the fiscal policy stance, i.e. whether there are fiscal expansions or adjustments. Our local projection results suggest that controlling for endogeneity of reforms and the stance of fiscal policy is crucial. To control for endogeneity, we use the Augmented Inverse Probability Weighted estimator. Our results suggest that product market reforms mostly cause slight negative growth, except when implemented during periods of neutral fiscal policy. Labour market reforms hurt growth under tight and neutral fiscal policy but are conducive to economic growth if introduced during periods of expansionary fiscal policy.
Keywords: E62; H30; J21; J65; L43; L51; O43; O47; 330; structural reforms; local projections; fiscal policy stance